INFLUENCE INTELLIGENCE EMOTIONAL AND RESILIENCE PSYCHOLOGICAL TO EFFECTIVENESS LEADERSHIP IN SOCIAL ORGANIZATION LEADERS - Frederick Rudy Sentosa Rajagukguk; Indra Welly Arifin; Hastuti Handayani Harahap (CV. Radja Publika, 2026)
This research aims analyze influence intelligence emotional and resilience psychological to effectiveness leadership in leaders organization social services in Tebing Tinggi City . This study is important Because organization social often face limitations source power , dynamics volunteers , pressure service society , as well as need taking quick and empathetic decisions . Research​ use approach quantitative with design survey explanatory . Research sample totaling 120 leaders organization selected social​ through purposive sampling based on experience lead at least one year . Data collected use questionnaire Likert scale and analyzed through validity , reliability and assumption tests classical , correlation , and multiple linear regression . Research results show that intelligence emotional influential positive and significant to effectiveness leadership (β = 0.413; t = 5.972; p < 0.001). Resilience psychological factors also have an influence positive and significant (β = 0.352; t = 5.083; p < 0.001) . simultaneous , both variables explains 54.9% of the variation effectiveness leadership . This finding confirms that ability understand emotions , managing pressure , adapt , and remain productive in situation difficult is factor important in increase quality leadership organization social .